IbM PELATIHAN PEMBUATAN MEDIA PEMBELAHARAN INTERAKTIF BERBASIS ICT BAGI GURU SDN DALANGAN 02 DAN 03 TAWANGSARI - Sari, Nurratri Kurnia; Purbosari, Para Mitta; Prasetyo, Koko; Angganing, Paradika (UNIVERSITAS PGRI MADIUN, 2021)
Abstract. Dalangan Elementary School 02 and 30 Tawangsari, Sukoharjo District, Sukoharjo Regency are located in the village of Dalangan, which is an in-depth area. School facilities such as LCDs, notebooks and even the internet already exist in several schools in the Merauke Cluster Elementary Schools in Nguter District, Sukoharjo Regency. The fact is that teachers are still few in using ICT media as a medium of learning, teachers in these schools still mostly use image media and conventional media. Whereas in every school, LCD and notebook are available. However, only a few teachers have not yet mastered the technology of making ICT-based media. The use of ICT media uses more exposure to power pints. The use of power points that is displayed is less interactive and tends to be exposive. So that the use of ICT media is not optimal. Based on these problems, the formulation of the problem to be answered is